Identifying efficient water storage schemes for climate change adaptation in agriculture: evidences from Indris Watershed in Ethiopia - Xenarios, Stefanos; McCartney, Matthew P.; Adenew, B. (2011)
Considerable research has been conducted into the technical adaptation measures that Ethiopian farmers might adopt to mitigate adverse climate change impacts. However, relatively little is known about Ethiopian farmers? perceptions of using water storage and land allocation to combat climate change. This paper assesses the major water and land related attributes which could be used to mitigate the impacts of climate change in agrarian regions of Ethiopia. The study was conducted in the Indris small irrigation system located northwest of Addis Ababa in Oromia region. The findings indicate that farmers prefer to utilize modern water canals in combination with large plots in lowland areas and high water consumption, even if they have to share half of their production in exchange.